ANALISIS HADITS TARBAWI PADA MATERI BUKU SISWA QUR’AN HADITS KELAS XI MADRASAH ALIYAH PASCA KMA NO. 185 TAHUN 2019: Analysis Of Tarbawi Hadith In Al-Qur'an Hadith Student Book Material For Class Xi Madrasah Aliyah Post KMA No.185 Of 2019 - Muhamad, Yusnawarman; Rif'an, Ali (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
The hadiths that are material in student books are things that students will fully believe in, because the book becomes a reference for learning. Considering the large number of false hadiths and hadiths with little truth circulating in society, researchers are interested in examining whether the hadiths in textbooks or student books are truly authentic hadiths. Apart from that, researchers are also interested in examining the content of hadiths from the perspective of tarbawi hadiths and analyzing the relevance of the hadith to the present. The aim of the research carried out is to determine the quality of the hadiths listed in the book so that readers can be more confident in believing in the hadiths studied. The method used in this research is a partial takhrijul hadith research method, so that one can understand the quality of the hadith from both the sanad and matan points of view. The type of research used is library research. The results of the research carried out are that in the first hadith, the hadith narrated by Ibn Majjah, whose quality is listed as Dho'if Lidzatihi, the second hadith, narrated by Ibn Majjah, has the quality Sahih Lidzatihi. The third hadith, a Hadith narrated by Imam Muslim, is Sahih Lidzatihi. And the hadiths studied have educational values that are relevant for current education, such as the value of faith education, moral education, reason education, psychological education, and social education.